Diversity and activity of sulphur‐oxidizing bacteria and sulphate‐reducing bacteria in landfill cover soils. (1st July 2014) - Xia, F.F.; Su, Y.; Wei, X.M.; He, Y.H.; Wu, Z.C.; Ghulam, A.; He, R.
Abstract: Sulphur bioconversion in landfill cover soils, including the metabolism of sulphur‐oxidizing bacteria (SOB) and sulphate‐reducing bacteria (SRB), is one of the important processes affecting H2 S emission from landfills. In this study, two landfills with or without landfill gas collection and utilization system were investigated to characterize the role of biotic and abiotic factors affecting diversity and activity of SOB and SRB in the landfill cover soils. The results revealed that the potential sulphur oxidation rates (SORs) and sulphate reduction rates (SRRs) varied with landfill sites and depths. SOR was significantly correlated with pH and SO4 2−, while SRR was significantly related with pH. The populations of both SOB and SRB were low in the acidic landfill cover soils (pH = 4·7–5·37). Cloning and terminal restriction fragment length polymorphism profiles of soxB and dsrB showed that SOB including Halothiobacillus, Thiobacillus, Thiovirga and Bradyrhizobium, and SRB including Desulfobacca, Desulforhabdus and Syntrophobacter dominated in the landfill cover soils, and their distributions were affected mainly by pH value and organic matter contents of soils. Significance and Impact of the Study: High diversity of sulphur‐oxidizing bacteria (SOB) and sulphate‐reducing bacteria (SRB) presented in the landfill cover soils. Among the physicochemical properties of soils (moisture content, pH, organic materials, SO4 2−, acid volatile sulphide and total sulphur), pH was the most important factor affecting the diversity and activity of SOB and SRB in the landfill cover soils. Higher pH of landfill cover soils (i.e. neutral or slight alkaline) was favourable for the growth of SOB and SRB, leading to a rapid bioconversion of sulphur. These findings are helpful to optimize sulphur biotransformation in landfill cover soils and to control odour pollution at landfills.